2009
DOI: 10.2214/ajr.08.2157
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Digital Mammography and Screen-Film Mammography in Breast Cancer Screening: A Review in the Irish Breast Screening Program

Abstract: FFDM resulted in significantly higher cancer detection and recall rates than screen-film mammography in women 50-64 years old. The PPVs of FFDM and screen-film mammography were comparable. The results of this study suggest that FFDM can be safely implemented in breast cancer screening programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
70
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 20 publications
8
70
0
3
Order By: Relevance
“…Full-field Digital Mammography (FFDM) is the current standard imaging technique for the early detection of breast cancer [1][2][3] and high quality, artefact free, diagnostic images are crucial to the accuracy of this process. Unwanted motion during the image acquisition phase and subsequent image blurring is an unfortunate consequence in some FFDM images.…”
Section: Introductionmentioning
confidence: 99%
“…Full-field Digital Mammography (FFDM) is the current standard imaging technique for the early detection of breast cancer [1][2][3] and high quality, artefact free, diagnostic images are crucial to the accuracy of this process. Unwanted motion during the image acquisition phase and subsequent image blurring is an unfortunate consequence in some FFDM images.…”
Section: Introductionmentioning
confidence: 99%
“…Oslo 2 study [4] , showed significantly higher cancer detection rate with FFDM in women between 45 and 69 years of age (5.9 versus 3.8 per 1000 (p = 0.002). Studies [5,6,8,17] done in the context of routine screening mammograms showed similar results. Del Turco et al [5] and Vigeland et al [6] compared SFM and FFDM in a local population based programme and found statistically higher detection rate for FFDM, which was marked for cancers presenting with microcalcification.…”
Section: Discussionmentioning
confidence: 59%
“…In our study, we found significantly more cases presenting with distortion, 13(16.2%) in the SFM group versus 10 (10%) in the FFDM group. We have not found many studies so far which shows difference in detection rate of distortion between SFM and FFDM, apart from a study by Hambly et al [8] which showed higher detection rate of FFDM secondarily to improved detection of distortion and microcalcification. This discrepancy could be related to small numbers presenting with distortion.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations